Comparison of pressure control ventilation with volume control ventilation in patients undergoing spine surgery in prone position: An open label randomized controlled trial - Poonam Godhwal; Renu Bala; Lalit Takia; Raj Singh (The Indian Anaesthetists' Forum)
Introduction: Evaluation and comparison of two modes of mechanical ventilation – volume control and pressure control in spine surgery in prone position in terms of respiratory mechanics (peak airway pressure [PAP], plateau pressure, lung compliance, dead space and oxygenation), hemodynamic parameters (heart rate and blood pressure), pulmonary function tests (vital capacity, peak expiratory flow rate, forced expiratory volume in first second). Materials and Methods: After obtaining approval from institutional ethics committee, the present prospective, randomized, single-blind study was conducted in 50 adult patients of either sex, American Society of Anesthesiologists I or II undergoing thoracic or lumbar spine surgery in prone position. Standard anesthesia protocols comprising of thiopentone, fentanyl and vecuronium were followed. Patients in volume control ventilation (VCV) group (n = 25) were ventilated with volume control mode with tidal volume (TV) = 7 ml/kg, positive end expiratory pressure = 5 cm H2O, I:E = 1:2 and respiratory rate varied to keep Et CO2 = 35–40 mmHg, FiO2 = 0.4. While in pressure controlled ventilation (PCV) mode (n = 25) patients were ventilated with similar settings except peak inspiratory pressure was adjusted to determine TV = 7 ml/kg. Pulmonary function tests were measured pre-operatively and post-operatively. Respiratory mechanics (PAP, lung compliance) and hemodynamic parameters were measured pre-, intra-, and post-operatively. Results: The demographic profile and surgical characteristics were similar between the groups. Peak inspiratory pressure was higher in VCV (20 vs. 18) and dynamic compliance low in VCV (31.3 vs. 35.93). Other parameters like dead space, minute ventilation, EtCO2 and oxygenation were comparable in the two groups. Postoperative PFT decreased in both groups but were comparable. Conclusion: This study found that intraoperative respiratory mechanisms were better maintained with PCV mode than VCV in patients undergoing thoracolumbar spine surgery in prone position although both offered similar pulmonary functions. Therefore, pressure mode can be a better alternative for ventilator strategy.